2021
DOI: 10.1016/j.jpsychores.2020.110350
|View full text |Cite
|
Sign up to set email alerts
|

A rapid review of the pathoetiology, presentation, and management of delirium in adults with COVID-19

Abstract: Background COVID-19 causes significant morbidity and mortality. Despite the high prevalence of delirium and delirium-related symptoms in COVID-19 patients, data and evidence-based recommendations on the pathophysiology and management of delirium are limited. Objective We conducted a rapid review of COVID-19-related delirium literature to provide a synthesis of literature on the prevalence, pathoetiology, and management of delirium in these patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
1
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 159 publications
2
64
1
14
Order By: Relevance
“…The cause of delirium is often multifactorial (e.g., infections, change in medications, use of restraints) especially in older patients [ 2 ]. In late 2019, a new emerging risk factor for delirium was the infection with SARS-COV2 [ 3 ]. The main hypothesis of the pathogenesis of delirium in patients with SARS-COV2 is a central neuroinflammation along with the worsening of other geriatric syndromes, which can be worsened by the infection itself or by the acute isolation related to the health care policies to reduce the spread of the viral infection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of delirium is often multifactorial (e.g., infections, change in medications, use of restraints) especially in older patients [ 2 ]. In late 2019, a new emerging risk factor for delirium was the infection with SARS-COV2 [ 3 ]. The main hypothesis of the pathogenesis of delirium in patients with SARS-COV2 is a central neuroinflammation along with the worsening of other geriatric syndromes, which can be worsened by the infection itself or by the acute isolation related to the health care policies to reduce the spread of the viral infection [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the occurrence of the SARS-COV2 pandemic, there has been an increasing interest in investigating the epidemiology of delirium. A recent review has reported how delirium affects up to 80% of the patients with SARS-COV2 in the ICU and between 29 and 67% in non-ICU patients [ 3 ]. Delirium in patients with SARS-COV2 is reported to increase the risk of mortality and worsen patients’ functional outcomes [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Siû lo ma lai ky tis iki pande mi jos eg zis ta vu siø so ma to ge ni nio de ly ro gy dy mo gairiø, jas pri tai kant kon kre èioms kli ni ki nëms si tu a ci joms, ak cen tuo jant kvë pa vi mo sis te mos pa þei di mus, ga li mas var to ja mø vais tø sà vei kas. Toks de ly ro gy dy mas pa pras tai re mia si jo es mi niø su de da mø jø da liø, t. y. su vo ki mo, màsty mo, psi cho mo to ri nio el ge sio, emo ci jø, mie go ir bud rumo cik lo bei ki tø su tri ki mø, ko rek ci ja [21].…”
Section: Diagnostika Gydymas Ir Prevencijaunclassified
“…Ma noma, kad imu no sup re suo tiems pa cien tams me la to ni nà reikë tø skir ti at sar giai [23]. Kli ni ki niø ty ri mø, pa tvir ti nan èiø me la to ni no efek ty vu mà de ly rui gy dy ti COVID-19 me tu, në ra [21,24].…”
Section: Diagnostika Gydymas Ir Prevencijaunclassified
See 1 more Smart Citation